The study of customers’ satisfaction towards client chartered in Hospital Alor Gajah - Bakar, Haslina (2004)
The study examines the level of customer satisfaction toward client chartered that should be practicing by Hospital Alor Gajah. This includes the response of the customer satisfaction toward the client chartered that should be practicing by Hospital Alor Gajah. In chapter I, this report will give details about the scope of study. This will include clear explanation about the study such as what is client chartered that have been established by Ministry of Health and client chartered of Hospital Alor Gajah itself. This chapter also about the objectives, scopes, significance and limitation of the study. Not forgotten, the key terms of the every sentence of the study. Chapter II is about the literature review of the study. This literature review will include the review of the research and the previous researches that have been done related to the study. This chapter also includes the hypotheses of the research that is the expected results. Chapter III is about the research methodology. In this chapter, it will describe the way the researcher is design the research such as the sample size, sampling techniques, the way of collecting data and data processing and analysis. The researcher will make a research toward 50 respondent of Hospital Alor Gajah using random sampling and stratified sampling. The researchers collect the data by making an observation and distributing the questionnaire to the clients of Hospital Alor Gajah. All data that was collected will be process by using Statistical Product and Services Solution (SPSS). In chapter IV, this report will show the results or findings of the research. The researcher is using frequencies and cross tabulation to report these findings. This chapter also includes the conclusion of the findings. Lastly, in chapter V, it is about the recommendation and the conclusion of the research. In this chapter, the researcher will give the recommendation related to the study in order to make Hospital Alor Gajah give 100% satisfaction to their clients.